Arrhythmogenic Right Ventricular Cardiomyopathy - Krahn, Andrew D; Wilde, Arthur A M; Calkins, Hugh; La Gerche, Andre; Cadrin-Tourigny, Julia; Roberts, Jason D; Han, Hui-Chen (JACC. Clinical electrophysiology, 2022)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) encompasses a group of conditions characterized by right ventricular fibrofatty infiltration, with a predominant arrhythmic presentation. First described in the late 1970s and early 1980s, it is now frequently recognized to have biventricular involvement. The prevalence is ∼1:2,000 to 1:5,000, depending on geographic location, and it has a slight male predominance. The diagnosis of ARVC is determined on the basis of fulfillment of task force criteria incorporating electrophysiological parameters, cardiac imaging findings, genetic factors, and histopathologic features. Risk stratification of patients with ARVC aims to identify those who are at increased risk of sudden cardiac death or sustained ventricular tachycardia. Factors including age, sex, electrophysiological features, and cardiac imaging investigations all contribute to risk stratification. The current management of ARVC includes exercise restriction, β-blocker therapy, consideration for implantable cardioverter-defibrillator insertion, and catheter ablation. This review summarizes our current understanding of ARVC and provides clinicians with a practical approach to diagnosis and management.